Design and development of bi-directional two stage battery charger for dual PV-grid - Yusoff Shazilly, Muhammad Imran (2017)
Throughout the evolutions of technology technology, various version of battery charger that are available commercially are built with various charging methods for harvesting solar power. However, there are various methods of battery charging that is implemented in the end-user products today that would give various side effects to the battery. This research presents the two stage bidirectional battery charger for dual PV- grid's design and development. The system implements two types of charging circuit which is the pulse charging sub-circuit and the float charging sub-circuit with the operation is controlled by an ATMega 2560 microcontroller loaded with Arduino. The implementation of Arduino software and libraries in AVR microcontroller significantly reduce the complexity of programming in order to create signals which provides charging algorithm and detects current and voltage for the charging circuit. In order to verify the expected outcome, the experimental hardware are developed and tested. The experimental data collection was performed to analyze the charging curve of the experimental hardware comparing with a commercial PWM charger where the system is proven to be able to charge efficiently without harming the battery life in the long run. With the C=7.2Ah, the results showed that the commercial PWM charger produces an output current as highest as 6.4A which equals to 0.9C charge rate while pulse charging sub-circuit only produces 1.8 A of maximum output current which equals to 0.25C. Thus, the proposed system of this research is able to charge lead acid battery efficiently within 0.25C of the maximum safe charging rate recommended and contributes to preserve the battery life in the long run.